Rodent species distribution and hantavirus seroprevalence in residential and forested areas of Sarawak, Malaysia - Nur Elfieyra Syazana, Hamdan; Yee, ling Ng; Wei, Bin Lee; Cheng, Siang Tan; Faisal Ali, Anwarali Khan; Yee, Ling Chong (Universiti Sains Malaysia, 2017)
Rodents belong to the order Rodentia, which consists of three families in Borneo (i.e., Muridae, Sciuridae and Hystricidae). These include rats, mice, squirrels, and porcupines. They are widespread throughout the world and considered pests that harm humans and livestock. Some rodent species are natural reservoirs of hantaviruses (Family: Bunyaviridae) that can cause zoonotic diseases in humans. Although hantavirus seropositive human sera were reported in Peninsular Malaysia in the early 1980s, information on their infection in rodent species in Malaysia is still lacking. The rodent populations in residential and forested areas in Sarawak were sampled. A total of 108 individuals from 15 species of rodents were collected in residential (n = 44) and forested (n = 64) areas. The species diversity of rodents in forested areas was significantly higher (H = 2.2342) compared to rodents in residential areas (H = 0.64715) (p < 0.001 of Zar-t test based on the Shannon index). Rattus rattus and Sundamys muelleri were present at high frequencies in both localities. An enzyme-linked immunosorbent assay (ELISA) showed that hantavirus-targeting antibodies were absent from 53 tested serum samples. This is the first report of hantavirus seroprevalence surveillance in rodent populations in Sarawak, East Malaysia. The results suggested that hantavirus was not circulating in the studied rodent populations in Sarawak, or it was otherwise at a low prevalence that is below the detection threshold. It is important to remain vigilant because of the zoonotic potential of this virus and its severe disease outcome. Further studies, such as molecular detection of viral genetic materials, are needed to fully assess the risk of hantavirus infection in rodents and humans in this region of Malaysia.